Fragilidade, quedas e autoeficácia em idosos brasileiros: dados da rede fibra - Renata Alvarenga Vieira (2013)
Frailty is a biological syndrome often associated with an increased risk of falling. Falls induce psychological conditions, commonly translated by the fear of falling. The cognitive component of fear of falling is often measured by means of the sense of self-efficacy. Reduction of self-efficacy to prevent falls is associated with activity restriction and subsequent functional decline. Thus, the fear of falling mediated by activity restriction triggers a cyclical relationship or a negative toward frailty in elderly spiral. Therefore, the aim of this study was to identify the prevalence of frailty and associated factors among elderly in the city of Belo Horizonte; determine the national prevalence of falls and associated factors in elderly patients with and without conditions of fragility and establish a cutoff score for self-efficacy to prevent falls that best differentiate elderly fallers and non-fallers of the factors associated with this cutoff point in individuals with or without conditions of fragility. Study populationbased evaluated 8608 community-dwelling elderly Brazilians aged 65 years. The phenotype of frailty, falls, self-efficacy related to falls, clinical, functional, sociodemographic, economic aspects and use of health services were evaluated. In multivariate analyzes set of ordinal regression models and Poisson. For analysis of sensitivity and specificity we used the ROC curve. Confidence intervals of 95 % (95 % CI) and = 0.05 were used. The results were presented in three studies. In the first, was identified in the city of Belo Horizonte the prevalence of pre-frailty of 46.3 % and 8.7% of frailty. The pre-frail and frail, respectively, showed higher and increasing odds ratio for dependency in instrumental activities of daily living (IADL); restrictions on advanced activities of daily living, use of walking aids, comorbidities, falls, depressive symptoms, lower self-efficacy for falls, hospitalization and advanced age. In the second study it was found 11.3% of frail elderly, 51.6 % pre-frail and non-frail 36.9%. The national prevalence of falls and recurrent falls in the elderly was 27.9 % and 14.1% and the frail elderly was 41.7% and 26.3%. In frail elderly factors associated with a larger number of falls were: fecal incontinence, memory deficits, hearing impairment, depressive symptoms, more medical visits, being single and not the owner of the residence. In the third study, the value of self-efficacy that best differentiates the sample according to the occurrence of falls was identified as 23 points in FES-I. IADL dependence, memory deficit, negative rated health, lower life satisfaction and being female were simultaneously associated in the elderly with and without conditions of fragility. The presence of comorbidities was the only factor simultaneously associated with pre-frail and not-frail elderly. Only the pre-frail elderly showed association of 23 points with socioeconomic conditions and number of medical visits. In non-frail elderly the point of cutoff of self-efficacy was singly associated with depressive symptoms and home visits. The results showed high rates of frailty associated with adverse health conditions, as well as high prevalence of falls in frail elderly.